Experimental Investigation on Post-tensioned Spannglass Beams during Temperature Loads - M. Engelmann (Challenging Glass Conference, 2016)
Recent research work focused on material efficient and safe structural use of glass beams. Reinforcing and post-tensioning of those structures in the style of reinforced concrete are promising options. They allow for a safe post-breakage behaviour of load bearing glass constructions. Other ductile materials such as steel and high-grade cables strengthen the glass, which results in robust structures. However, hybrid structures are prone to temperature loads. Especially post-tensioned glass beams – Spannglass Beams – are vulnerable to lose part of their initial cable load caused by a different expansion of their parts. The thermal expansion coefficient of steel cables is about 70% larger than the value of glass. Therefore, a cable in a hybrid structure will expand much more during heating. This effect results in a loss in initial cable load of a post-tensioned reinforcement, and cannot be prevented. Hence, the temperature dependency needs to be considered during the design stage. Furthermore, a change in temperature influences the material properties of glass-contact materials and the interlayer. Thermoplastic blockings transfer the cable load into the laminated glass edge. Due to manufacturing tolerances, the interlayer material is stressed. Therefore, this will affect the reaction of the structure to a change in temperature. The non-destructive experimental study includes the results of a set of two Spannglass Beams with 8 mm post-tensioned cables. Adhesively bonded connectors redirect the cables according to the needs in a four-point bending set-up. Two-meter long beams were placed in a climate chamber to heat the specimens from ambient temperature to 60°C. We recorded the structural behaviour at alternating initial cable loads as well as different bending loads. Finally, the results led to a recommendation on how to consider a possible loss in cable load caused by a change in temperature. This will support the argumentation that post-tensioning glass beams is a feasible structural option.